2019
DOI: 10.3897/jhr.73.39136
|View full text |Cite
|
Sign up to set email alerts
|

First report of Telenomus remus parasitizing Spodoptera frugiperda and its field parasitism in southern China

Abstract: The fall armyworm, Spodoptera frugiperda, is a lepidopteran pest that feeds on many economically important cereal crops such as corn, rice, sorghum, and sugarcane. Native to the Americas, it has become a serious invasive pest in Africa and Asia. Recently, this pest was found in China and has spread quickly across the country. As S. frugiperda will most likely become a major pest in China, Integrated Pest Management strategies, including biological control methods, should be developed to manage its populations.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 8 publications
2
16
0
2
Order By: Relevance
“…Although T. remus is frequently cited as a promising augmentative biological control agent against FAW in Africa and Asia [6,[26][27][28][29], few publications provide solid data to assess the efficacy of the method under natural infestation conditions. This is the first published study outside the native range of the pest describing trials in farm conditions and assessing the impact on naturally occurring FAW populations during two maize growing seasons.…”
Section: Discussionmentioning
confidence: 99%
“…Although T. remus is frequently cited as a promising augmentative biological control agent against FAW in Africa and Asia [6,[26][27][28][29], few publications provide solid data to assess the efficacy of the method under natural infestation conditions. This is the first published study outside the native range of the pest describing trials in farm conditions and assessing the impact on naturally occurring FAW populations during two maize growing seasons.…”
Section: Discussionmentioning
confidence: 99%
“…New records of Te. remus on the African continent [ 29 , 30 ] and in China [ 31 ] were mainly taken from recent reports. Presence records used for all the six modeled species are provided in Files S1-6.…”
Section: Methodsmentioning
confidence: 99%
“…The continuing spread of fall armyworm (FAW), Spodoptera frugiperda (J E Smith) (Lepidoptera, Noctuidae) to new ecological niches raises regional and global concerns. An updated literature review and surveys recently indicated a total of 353 FAW larval host plant records belonging to 76 plant families, chiefly Poaceae (106), Asteraceae (31) and Fabaceae (31) [2]. However, the most preferred host of the pest is maize.…”
Section: Introductionmentioning
confidence: 99%
“…In the Americas, FAW is attacked by an assemblage of parasitoids (approximately 150 species) [ 22 , 23 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. Across the invasive range of FAW, several parasitoids have been identified (e.g., China [ 34 ]; India [ 35 , 36 ]). In Africa, reports of parasitoids attacking FAW have come from South Africa, Côte d’Ivoire, Ethiopia, Kenya, Niger, Benin, and Tanzania [ 37 , 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%